Islamic Financial Technology Usage: An Investing Perspectives On Generation Z - Oktavendi, Tri Wahyu (Universitas Muhammadiyah Surakarta, 2020)
Today, in Sharia Finance Sector, there was some a new model of sharia finance based on Financial Technology, it is called Islamic Financial Technology (I-Fintech). In other side, A Generation Z comes up as consumer of I-Fintech in the future. There is a big question like “do Generation Z accept I-Fintech in the future?”. Using Technology Acceptance Model with 3 proxy, it is Perceived Usefulness, Perceived Ease of Use, and Attitude Toward Using. The result of this research show that Perceived Usefulness and Perceived Ease of Use affect on Attitude Toward Using I-Fintech. The conclusion is Generation Z’s perceived on I-Fintech are depend on its usefulness and ease of use. This result implied on the development focus of I-Fintech in the future.